COOKIES UNTUK MENCEGAH STUNTING - Arfiyanti Arfiyanti (JURNAL KIMIA SAINTEK DAN PENDIDIKAN, 2021)
Stunting is short stature, one of which is caused by the cumulative process of nutritional deficiency of 1000 HPK. It is necessary to provide food fortified with multi micro and macro nutrients and ligands for pregnant women. The purpose of the study was to obtain a cookie fortification formulation according to the needs of pregnant women. Research method : The research on cookie formulation consisted of making flour (tuna fish, snakehead fish, beef, chicken, banana, green beans, tempeh), followed by a composite flour formulation. Composite flour optimization method with D-optimal RSM mixture design using Design Expert 7.0 trial software (DX 7 trial). The composite flour formula was selected based on the nutritional content and taste. Substitution of rice flour with selected composite flour in the standard recipe. Results: The content of protein, energy, vitamin A, vitamin B12, calcium, phosphorus, Zn, Iodine, Folic acid in the four cookies met the nutritional adequacy rate (RDA) for pregnant women in the second trimester. The levels of vitamin C and Fe are smaller than the RDA. Cookies contain ligands, are round in shape, have aroma, taste, color, appearance similar to cookies in general and are in accordance with SNI01-2891-1992,BUTIR1.2. Cookies meet the microbiological requirements of BPOM and are preferred by pregnant women in the second trimester, based on organoleptic tests. Conclusion: The four cookies can be used as additional food for pregnant women to accompany the government supplementation program.